2022
DOI: 10.29303/jppipa.v8i3.1627
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Ornamental Plants Via Google Lens Based on Intersemiotic

Abstract: This research aims to develop a feasibility test and practical application of biology learning media technology, especially in terms of taxonomy introduction via google lens. The experimental method was used to collect identification data regarding intersemiotic translation of ornamental plants. The stage to find out the quality of intersemiotic translation of the research object using a google lens in the form of the general method of photo analysis in the use of google lens using the keys of google lens resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…This screening application would capture retinal images using Google Lens or automatically become linked to Google Lens. Google Lens [28,36], being a vision-assisted AI tool, would then search the web or dedicate DR image libraries to find an appropriate match. This match would then inform the patient about the grade of DR, including no DR, mild DR, moderate DR, severe DR, and presence/absence of DME [30].…”
Section: Future and Implications Of Google Lens-based Dr Screeningmentioning
confidence: 99%
“…This screening application would capture retinal images using Google Lens or automatically become linked to Google Lens. Google Lens [28,36], being a vision-assisted AI tool, would then search the web or dedicate DR image libraries to find an appropriate match. This match would then inform the patient about the grade of DR, including no DR, mild DR, moderate DR, severe DR, and presence/absence of DME [30].…”
Section: Future and Implications Of Google Lens-based Dr Screeningmentioning
confidence: 99%
“…Masropah et al (2022) concluded that learning biology on plant concepts using Google Lens really helps students in constructing their own knowledge, apart from being able to analyze digital literacy skills, it can also improve student activities and learning outcomes (Sofian et al, 2022). Google Lens is the most recommended application for the process of plant identification in biology learning (Nuraini et al, 2022;Shapovalov et al, 2019). Not only Google Lens, other similar applications are used by Sugandi et al (2020) namely the Pl@ntNet application, Kumar et al (2012)) with Leaf Snap application, and Hannah et al (2020) with the Picture This application which showed that the application used in the study had a good performance in identifying plants.…”
Section: Introductionmentioning
confidence: 99%
“…The role of the agricultural sector in the economy of a country or a region can be seen from several aspects. The contribution of the agricultural sector to the Gross Domestic Product (GDP) or to the Gross Regional Domestic Product (GRDP) (Nuraini et al, 2022;Muskitta et al, 2023). The contribution of the agricultural sector to employment opportunities.…”
Section: Introductionmentioning
confidence: 99%